EFEKTIVITAS INSTAGRAM SEBAGAI MEDIA PROMOSI HIDDEN STRAWBERRY GARDEN, BALI - Vidi Christanti, Rai Olivia; Kusuma Negara, I Made; Wikanatha Sagita, Putu Agus (Jurnal IPTA (Industri Perjalanan Wisata), 2024)
This research is motivated by the increasing competition in the tourism industry and changes in visitor preferences who tend to be more digital-savvy. Hidden Strawberry Garden needs to ensure that its promotional strategy through social media is effective in attracting and maintaining visitor interest. It is hoped that Hidden Strawberry Garden’s use of Instagram can increase awareness and interest in visiting, as well as provide complete and useful information for potential visitors. However, to assess how effective Instagram is as a promotional tool for Hidden Strawberry Garden, it is necessary to carry out in-depth measurements and analysis. It is important to understand that the success of tourism promotion via social media is not only seen from the number of visitors who succeed in attracting their interest, but also from how well the information conveyed can guide potential visitors in preparing for their visit. The aim of this research is to analyze the characteristics of visitors who visit the Hidden Strawberry Garden Agro-edutourism. To analyze, measure and determine the effectiveness of social media Instagram @strawberry_corps as a promotional media for Agro-edutourism Hidden Strawberry Garden Pancasari, Buleleng, Bali. This research uses qualitative and quantitative methods. Data was collected using literature studies, questionnaires, interviews and documentation. The respondents in this study were 100 respondents with the criteria for respondents being Instagram users who visited the Instagram account @strawberry_corps, Instagram users aged over 17 years. After calculating the overall average of the AIDA variables (Attention, Interest, Desire, Action), it shows that Instagram social media has proved to be very effective as a promotional media.